MEDIA GAME EDUKASI TERHADAP KEMAMPUAN BAHASA RESEPTIF PADA ANAK USIA 5-6 TAHUN - Azis, Mislia; Upu, Hamzah; Syamsuardi Syamsuardi; Wahira Wahira (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to find out the description of the application, children's receptive language skills before and after the application of educational game media, as well as the influence of educational game media on children aged 5-6 years, the description of children's receptive language skills before and after the application of digital educational game media in children aged 5-6 years. The type of research used is quantitative research, with an Ex Post Facto approach. The data collection technique uses performance tests, observations, and documentation. The data analysis technique uses a data normality test. The results of the study show that first, the application of educational game media in children aged 5-6 years shows that children's ability to carry out lessons with the use of educational game media is in the category of high tendencies, with most children who have scores being around the average score. This condition shows the existence of a representative nature between children aged 5-6 years which is used as a research sample., second, children's receptive language skills before using educational game media can be relatively low because there is no special media that significantly helps the development of receptive language skills of children aged 5-6 years. After using educational game media in learning, the receptive language ability of children aged 5-6 years experienced significant changes based on the results of the study stating that the positive influence given from educational game media showed that learning with educational game media had a significant effect on the receptive language ability of children aged 5-6 years. A positive regression coefficient of 1.920 indicates that any increase in the application of learning through educational game media is followed by an improvement in children's receptive language skills.